2016
DOI: 10.5216/ree.v18.35523
|View full text |Cite
|
Sign up to set email alerts
|

Desafios no cuidado às complicações agudas do diabetes mellitus em serviço de emergência adulto

Abstract: O diabetes mellitus impõe múltiplos desafios às pessoas afetadas, suas famílias e ao sistema de saúde. Teve como objetivo analisar fortalezas e fragilidades no atendimento de enfermagem às complicações agudas do diabetes mellitus num serviço de emergência adulto. Pesquisa qualitativa do tipo descritivo-exploratória, realizada entre maio e julho de 2013, mediante entrevistas semiestruturadas com 18 profissionais de enfermagem de um hospital do sul do Brasil. Para organização e análise dos dados, elencaram-se ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
5
0
5
Order By: Relevance
“…Many studies have presented the theme of economic evaluation focused on the care provided by the pharmacist, such as pharmaceutical care, which uses methods such as MTM and patient empowerment [22,44]. Pharmaceutical care in a program for the elderly with T2DM and systemic arterial hypertension followed in primary health care in a municipality in the interior of the state of São Paulo, showed that the implementation of pharmaceutical care does not add significant costs to the health service when compared to the results of the best outcomes achieved in patient care [35].…”
Section: Diabetes and Its Complications 170mentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have presented the theme of economic evaluation focused on the care provided by the pharmacist, such as pharmaceutical care, which uses methods such as MTM and patient empowerment [22,44]. Pharmaceutical care in a program for the elderly with T2DM and systemic arterial hypertension followed in primary health care in a municipality in the interior of the state of São Paulo, showed that the implementation of pharmaceutical care does not add significant costs to the health service when compared to the results of the best outcomes achieved in patient care [35].…”
Section: Diabetes and Its Complications 170mentioning
confidence: 99%
“…This stage of care is directed mainly to the direct costs. The glycemic value can be considered an intermediate outcome, and thus, health technologies capable of reducing glycemia have been tested in cost-effectiveness analysis to verify the efficiency of DM care [4,5,22].…”
Section: Costs Associated With the Treatment Of Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Universidade Federal de Santa Catarina, Programa de Pós-Graduação em Enfermagem, Florianópolis, SC, Brasil. Correio eletrônico: vipecini@gmail.com 3 Enfermeira. Doutora em Filosofia da Enfermagem.…”
Section: Introductionunclassified
“…Viviane Pecini da Cunha 2 , Alacoque Lorenzini Erdmann 3 , José Luís Guedes dos Santos 4 , Fernando Henrique Antunes Menegon 5 , Keyla Cristiane do Nascimento 6 Institução: Universidade Federal de Santa Catarina…”
unclassified